Evaluation of bread wheat (Triticum aestivum) genotypes under organic farming in north-west India - AULAKH, C S; SIDHU, A S; NARA, USHA; SINGH, SURINDER; SINGH, SUKHVEER (The Indian Journal of Agricultural Sciences, 2022)
The productivity of wheat (Triticum aestivum L.) generally remains low under organic farming in north-west India. Being a major crop under organic farming in in this region, the genetic variation among the wheat varieties/genotypes needs to be exploited for better nutrient use efficiency and higher productivity. The present experiment was conducted during winter (rabi) season 2018–19 and 2019–20 at research farm of Punjab Agricultural University, Ludhiana, Punjab to evaluate 9 bread wheat varieties, viz. PBW 1 Zn, PBW 175, PBW 660, Unnat PBW 343, Unnat PBW 550, PBW 1 Chapati, C-306, BWL 3498 and BWL 3500 for better profitability under organic farming. The highest grain yield was recorded with wheat variety Unnat PBW 550 which was statistically at par with PBW 1 Chapati, BWL 3498 and Unnat PBW 343 varieties but significantly better than PBW 1 Zn, C 306, BWL 3500, PBW 175 and PBW 660 varieties. The lowest grain yield was recorded with variety PBW 1 Zn. Similar trend was observed for biological yield and yields contributing characters, viz. effective tillers, number of grains/spike and test weight. The net returns and benefit-cost (B:C) ratios were also the maximum with variety Unnat PBW 550 as compared to all other varieties/ genotypes. The study concluded that wheat variety Unnat PBW 550 performed better than all other varieties under organic farming and can be recommended to organic growers of the state.